Letterland; vocabulary; language learning; language teaching - . Budianto; Elis Munawaroh; Fitri Anggraini; Yuni Arifah (Bandar Lampung University, 2015)
Vocabulary is one of elements which isimportant in language learning. Teaching vocabulary requires an effective way especially for teaching children. The paper describes the application of using Letterlandtechnique for teaching children English vocabulary. Participants are students at Elementary school of MIMA 7 LabuhanRatu Grade 2, Bandar Lampung. It is found that there is good influence of using letterlandtechnique towards the students’ vocabulary mastery.